Antifungal Activity of Ethanolic Extracts from Aeroponically Grown Cape Gooseberry (Physalis peruviana L.) with LED Lights and In Vitro Habituated Roots - Daniel Eduardo Avila-Avila; Martha Alicia Rodríguez-Mendiola; Carlos Arias-Castro; Laura Isabel Arias-Rodríguez; Martin Eduardo Avila-Miranda; Norma Alejandra Mancilla-Margalli (Plants)
Green mold caused by Penicillium digitatum is a major post-harvest disease in citrus fruits. Therefore, the search for sustainable and low-environmental-impact alternatives for the management of these fungi is of utmost importance. Physalis peruviana L. is a native fruit of the Peruvian Andes with rich bioactive components present throughout the plant. Its antifungal activity stands out, attributed to its high content of phenols, coupled with its antioxidant capacity and antimicrobial activity. Plants were cultivated aeroponically under a combination of red, mixed (50% red, 50% blue), and green LED lights. Additionally, in vitro-habituated roots free of plant growth regulators were also cultivated. An ethanol extraction assisted by ultrasound for 30 min followed by maceration for 72 h was performed, and the extract was filtrated and evaporated in an extraction hood. Antioxidant activity was assessed using the DPPH method, total polyphenols were measured using the Folin–Ciocâlteu method, and an antifungal test in vitro by the poisoned food method was conducted against P. digitatum. In vitro assays revealed that extracts from leaves, roots, and fruits exerted a significant inhibitory effect on the growth of P. digitatum, as evidenced by a reduction in colony radius when cultured employing the poisoned food method, with IC50 values of 62.17, 53.15, and 286.34 µg·mL−1, respectively, compared to 2297 µg·mL−1 for the commercial fungicide Captan 50WP. Although leaves had higher total polyphenol content, no direct correlation with antifungal activity was found. Colored LEDs enhanced phenol accumulation, antioxidant capacity, and antifungal properties in plant parts compared to white LEDs and in vitro roots. These findings suggest P. peruviana as a new alternative biological production system to provide natural compounds for post-harvest disease management.